Probabilistically shaped amplitude and pulse position modulation based on stepped amplitude probability distribution for optical access networks. Issue 2 (22nd September 2020) - Zhang, Jingyi; Liu, Bo; Mao, Yaya; Ren, Jianxin; Xu, Xing; Wu, Xiangyu; Song, Xiumin; Jiang, Lei; Han, Shun; Zhao, Jianye
Abstract: We propose a novel probabilistically shaped amplitude and pulse position modulation (APPM) based on stepped amplitude probability distribution for optical access networks. By adopting the probabilistic shaping (PS) technique, average signal power can be reduced and better bit error rate (BER) performance obtained. The proposed PS‐APPM scheme has been successfully verified in a 25‐km standard single‐mode fiber (SSMF). Experiment results show that at a BER of 1 × 10 −3, the proposed 4 × 16 APPM‐PS1 and 4 × 16 APPM‐PS2 outperform the traditional 4 × 16 APPM by 1.54 and 2.52 dB receiver sensitivity improvement, while the proposed 8 × 8 APPM‐PS1 and 8 × 8 APPM‐PS2 excel the traditional 8 × 8 APPM by 2.1 and 3.5 dB at a BER of 1 × 10 −2, suggesting the advanced nature of the proposed scheme for future optical access networks.